Política pública de seguridad ciudadana referente a la regulación de bebidas alcohólicas, en el Distrito Metropolitano de Quito y su relación con el control del delito: caso circuito La Mariscal, 2009-2013 - Riera Mendoza, Luis Sebastián (2018)
The present research analyzes how the implementation of the public policy of public safety regarding the regulation of alcohol impacts on the control and prevention of crime through the indicators of citizen security. Based on the above, a case study was carried out in the Mariscal Circuit, in the Metropolitan District of Quito, starting from the hypothesis that the public policy of alcohol regulation would have a relation that allows to influence certain crimes associated with it homicide / murder and robbery. In order to test this hypothesis, three specific objectives were set out to describe and analyze the effect of the public policy of alcohol regulation, in order to determine its outcome with respect to the prevention or reduction of certain levels of crime, for which it was considered pertinent to carry out a mixed descriptive research and use as research techniques the analysis or documentary study and interviews.